Clinical characteristics of pediatric patients with confirmed SARS-CoV-2 infection who followed rigorous measures during two years of the COVID-19 pandemic in a hospital in Mexico - Ramírez-Cázares, Ana Carolina; Hernández-Ruíz, Yodira Guadalupe; Martínez-Longoria, César Adrián; Tamez-Gómez, César Eduardo; Medina-Macías, Obed; Treviño-Montalvo, Roberto Guadalupe (Frontiers in Pediatrics, 2023)
Background: COVID-19 infections have been described as asymptomatic or mild, with a low incidence of severe cases in children and adolescents who followed the basic hygiene measures. The objective of this study was to describe the clinical and epidemiological characteristics of our pediatric population during four waves of the COVID-19 pandemic from a private hospital. Methods: A retrospective observational study in patients under 15 years old with confirmed SARS-CoV-2 infection by real-time reverse transcription-polymerase chain reaction (RT-PCR) test from April 1, 2020, to April 30, 2022. Demographic, clinical, and therapy variables were examined, and the Chi-square test was used for comparisons. Results: From 5,870 RT-PCR taken through the first two years of the pandemic, 1,371 tested positive, obtaining a positivity rate of 23.37%. Patients' median (IQR) age was 9.0 (7.0) years, and most were male (n=705, 51.4%). The primary comorbidities were rhinitis (n=239,17.4%) and asthma (n=172,12.5%). Most cases were scholars (n=568,41.4%) during the fourth COVID-19 wave (n=831,60.6%). Almost all cases (88.2%) reported prior exposure to SARS-CoV-2-infected households. Six percent (n=82) of the patients reported being vaccinated against SARS-CoV-2. Most participants (89.3%) received outpatient care, and 0.6% required hospitalization. Nine (0.6%) patients were diagnosed with Multisystemic Inflammatory Syndrome in Children (MIS-C). The second COVID-19 wave reported a higher frequency of anosmia and dysgeusia; the third wave reported fever and malaise, and the fourth wave reported cough, odynophagia, and vomiting (p<0.05). The second wave reported no treatment (n=23, 15.3%), while the third and fourth waves reported outpatient care and hospitalization (n=367, 95.1%; and n=4, 1.0%, respectively)(p=<0.001). Reinfection cases were frequent during the second wave (n=8, 5.3%)(p=<0.001). Rhinorrhea, vomiting, and diarrhea were reported mainly by infants; fever by preschoolers; abdominal pain by scholars; and headache, odynophagia, anosmia, dysgeusia, myalgia, arthralgia, and malaise by adolescents (p<0.05). Neither treatment nor reinfection showed age-related differences (p=0.496 and p=0.224, respectively). Conclusion: The study demonstrated a lower positive rate for SARS-CoV-2 in our hospital. The majority of cases in our study were outpatients who reported a mild infection with a favorable evolution based on symptomatic treatment.